2018
DOI: 10.1007/s11356-018-1490-8
|View full text |Cite
|
Sign up to set email alerts
|

Macroelements and heavy metals content in energy crops cultivated on contaminated soil under different fertilization—case studies on autumn harvest

Abstract: Heavy metals (HMs) contamination of soils is a major problem occurring worldwide. Utility of energy crops for biofuel feedstock production systems offers a feasible solution for a commercial exploitation of an arable land contaminated with HMs. Experiments involved field testing of Miscanthus x giganteus and Spartina pectinata cultivated on HMs-contaminated soil with standard NPK fertilizers and commercially available microbial inoculum. Biomass yield, water content, macronutrients (N, P, K, Mg, Ca), and heavy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 38 publications
3
27
0
Order By: Relevance
“…Microorganisms support the use of soil macronutrients by plants [Pogrzeba et al 2018]. Our ex-periment yielded high values of the activity of the tested enzymes, which confirms the effectiveness of the use of sewage sludge as an organic fertilizer in the cultivation of energy crops [Kołodziej et al 2015;Wolna-Murawka et al 2018].…”
Section: Enzymatic Activitysupporting
confidence: 79%
See 2 more Smart Citations
“…Microorganisms support the use of soil macronutrients by plants [Pogrzeba et al 2018]. Our ex-periment yielded high values of the activity of the tested enzymes, which confirms the effectiveness of the use of sewage sludge as an organic fertilizer in the cultivation of energy crops [Kołodziej et al 2015;Wolna-Murawka et al 2018].…”
Section: Enzymatic Activitysupporting
confidence: 79%
“…According to Molas [2012, 2013] as well as Krzywy-Gawrońska [2012], the increase in the content of macroelements in energy plants is determined by the dose of sewage sludge and mineral fertilization, which was also confirmed by our study. Pogrzeba et al [2018] indicated that mineral fertilization and the addition of microorganisms increased the macroelement content in the selected energy crops, which was confirmed by us. As stated by Wierzbowska et al [2016] and Krzywy-Gawrońska [2012], increasing the doses of sewage sludge raised the contents of N, P, K, Na, Ca, and Mg in the Virginia fanpetals, which confirms that this species is very effective in the use of macronutrients from these wastes.…”
Section: Macroelement Contentsupporting
confidence: 76%
See 1 more Smart Citation
“…Only available forms of these nutrients can be taken up by plants (Tkaczyk et al 2017, Symanowicz et al 2018 in the authors' own research presumably resulted from the lower yield, and thereby from a higher 'concentration' of nutrients in the plant biomass. Other authors' studies confirm that plants with higher yields are characterized by the 'dilution effect', hence the lower content of the analyzed elements in the plant biomass can be explained (Antonkiewicz et al 2018, Pogrzeba et al 2018, Witkowicz et al 2015. The value of the concentration index (CI) indicates that reed canary grass took up Na and Ca from sewage sludge more intensely.…”
Section: Macronutrient Contentmentioning
confidence: 92%
“…It displays large biomass yield and is successfully cultivated worldwide for renewable energy production [18,19]. Comprehensive investigations into its heavy metal accumulation and its potential use for aided phytoremediation of heavy metal polluted soils, fly ash or technosols have been performed [20][21][22][23][24][25][26]. However, there is little information on its growth in the flotation tailings and its possible cultivation for their phytostabilization [27,28].…”
Section: Introductionmentioning
confidence: 99%